Empirical Analysis of Risk Behavior in Truck Drivers Across Industrial Zones and Policy Recommendations - Seefong, Manlika; Wisutwattanasak, Panuwat; Se, Chamroeun; Banyong, Chinnakrit; Theerathitichaipa, Kestsirin; Jomnonkwao, Sajjakaj; Champahom, Thanapong; Ratanavaraha, Vatanavongs; Kasemsri, Rattanaporn (Salehan Institute of Higher Education, 2025)
Truck drivers play a crucial role in industrial development but face disproportionately high risks of traffic-related injuries and fatalities. These risks arise from complex traffic conditions, especially in truck-congested industrial zones, and economic pressures that encourage risky driving behaviors. This study investigates key factors influencing these behaviors among truck drivers in industrial zones using an integrated framework combining the Health Belief Model and Protection Motivation Theory, a novel approach in this context. A random parameter model was employed to account for unobserved heterogeneity in drivers’ responses. The results highlight several significant psychological factors: perceived susceptibility (when drivers perceive the risk of crashes while driving), perceived severity (when drivers feel that crashes will impact their work), perceived barriers (when truck drivers perceive that fastening seat belts causes discomfort and when they perceive safety equipment for vehicles as expensive and unaffordable), cues to action (when truck drivers encounter safe driving campaigns), and health motivation (when truck drivers prioritize adequate rest and relaxation). Additionally, the study identifies route familiarity as a random effect, revealing variations in how this factor influences behavior across individuals. The study provides practical, evidence-based policy recommendations aimed at reducing road injuries and fatalities among truck drivers, offering valuable insights for policymakers, transport authorities, and logistics stakeholders.